Effects of drying on pumpkin and green peper colour. - Guiné, Raquel (2013)
The present work evaluates the effect of different drying treatments on the colour of green bell peppers and pumpkin, which were dried using two different methods: air drying and freeze-drying. The treatments in air drying were carried out at 30 ºC and 70 ºC. Overall, it was possible to conclude that air drying at 30 ºC produces small changes in colour of green pepper whereas air drying at 70 ºC and freeze drying originate more intense colour changes. The increase of temperature on air drying augments the colour saturation of dried pumpkin while decreases the hue angle by a linear relationship. In addition, the chroma of dried pumpkin decreases significantly with the freeze drying, while the hue angle is maintained constant as compared with the fresh vegetable.